Decomposition of ethelene in low temperature plasma of barrierless discharge - Golota, V.I.; Kudin, D.V.; Manuilenko, O.V.; Taran, G.V.; Zavada, L.M.; Yegorov, M.O.; Khmelevskaya, V.F. (Вопросы атомной науки и техники, 2018)
The experimental setup for investigation of conversion the ethylene impurity in the air on the basis of automated container systems, which using for storing and transporting vegetables and fruits, was developed and tested. The high efficiency of using a barrierless gas discharge to conversion the ethylene impurity in the air experimentally confirmed.